HUBUNGAN PENERAPAN ISO 9001:2000 DAN ORGANISASI BELAJAR TERHADAP KINERJA STAF - Elais Retnowati; Sutaryat Trisnamansyah (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
The objective of this research is to analyze the relationship of ISO 9001:2000 implementation with the learning organization and the staff performance in an institution. This study is conducted in P2PNFI Region I Jayagiri and P2PNFI Region II Semarang. The design of development strategies on this research are: (1) conducting the beginning study; (2) creating research instruments; (3) testing instruments; (4) analyzing the validity and reliability instruments; (5) distributing questioners to 94 respondents at P2PNFI Regional I Jayagiri and 84 respondents at P2PNFI Regional II Semarang; (6) collecting questioners; (7) data input and processing; (8) conducting data analyzing and (9) wrapping up the conclusion. The research reveals that (1) there is an increase of the staff performance; (2) a positive correlation between the implementation of ISO 9001:2000 with the staff performance; (3) a positive relationship between the learning organization with the staff performance and (4) a correlation between the implementation of ISO9001:2000 with the performance of staff at two institutions.